Respon Eksplan Batang (Caulis) Planlet Tanaman Duku (Lansium domesticum Corr.) Terhadap Pemberian Kinetin Pada Media Murashige Skoog Melalui Kultur Jaringan - YACHYA, ARIF; Nurokhman, Amin; Rasinta, Nanda (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2024)
The duku plant (Lansium domesticum Corr) is a plant that is widely distributed in tropical regions such as Indonesia. One of the famous plants in Indonesia is duku Komering. Duku has a very sweet taste with proven production increasing every year. So it is necessary to cultivate duku using tissue culture techniques. The use of tissue culture techniques is able to produce seedlings in large quantities in a short time. This research aims to see the response of stem explants from plantlets. The research was carried out in the Tissue Culture room, Integrated Laboratory, Raden Fatah State Islamic University, Palembang for 49 days after induction (DAI). The type of research used is qualitative descriptive research and experimental methods with a completely randomized research design (CRD). This research used several varying concentrations of kinetin, including 0 ppm, 1 ppm, 2 ppm, 3 ppm and 4 ppm. on stem explants (caulis) from duku plantlets (Lansium domesticum Corr.). The results showed that there was no growth response to the administration of various concentrations of kinetin during the observation